2004
DOI: 10.1111/j.0361-3666.2004.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in HIV/AIDS/STI Knowledge, Attitudes and Practices among Commercial Sex Workers and Military Forces in Port Loko, Sierra Leone

Abstract: Sierra Leone suffered from 11 years of civil war (1991-2002) resulting in tens of thousands of deaths and mutilations together with massive population displacement. In 2001, ARC International, Sierra Leone conducted a baseline survey of 201 commercial sex workers (CSWs) and 202 military respondents on the knowledge, attitudes and practices surrounding HIV/AIDS and STIs in Port Loko, Sierra Leone. In 2003, a comparable post-intervention survey of 202 CSWs and 205 military respondents was performed. Comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…The interviewees, including military authorities, were willing to respond to questions addressing human resources, functioning of health facilities and HIV/AIDS issues. Our observation that health-related research can be pursued in the aftermath of an armed conflict, which indeed facilitates assessment and quantification of conflict impacts, is consistent with recent reports from other conflict zones across Africa (Ahuka et al , 2004;DeLargy & Alakbarov, 2004;Larsen et al , 2004;O'Heir, 2004;Sodemann et al , 2004;Tangermann et al , 2000). Perhaps the most extreme example arises from the first nationwide cross- sectional survey carried out 18 months after the March 2003 invasion of Iraq.…”
Section: Discussionsupporting
confidence: 90%
“…The interviewees, including military authorities, were willing to respond to questions addressing human resources, functioning of health facilities and HIV/AIDS issues. Our observation that health-related research can be pursued in the aftermath of an armed conflict, which indeed facilitates assessment and quantification of conflict impacts, is consistent with recent reports from other conflict zones across Africa (Ahuka et al , 2004;DeLargy & Alakbarov, 2004;Larsen et al , 2004;O'Heir, 2004;Sodemann et al , 2004;Tangermann et al , 2000). Perhaps the most extreme example arises from the first nationwide cross- sectional survey carried out 18 months after the March 2003 invasion of Iraq.…”
Section: Discussionsupporting
confidence: 90%
“…The need for this knowledge is urgent, given that the epidemic is still largely confined within high-risk populations but has the potential to quickly spread to the general population. Although condom use by FSWs has been studied extensively in other parts of the world (Basuki et al, 2002;Ward et al, 2004;Larsen et al, 2004;Witte et al, 2000), little information is available on FSWs in Vietnam. In our previous qualitative study among FSWs in Hanoi (Tran et al, 2004), they reported higher condom use with irregular clients, although use was still low with regular clients and their love mates.…”
Section: Introductionmentioning
confidence: 99%
“…When studied, military personnel worldwide have been documented as frequently engaging in transactional sex and inconsistently using condoms with casual and commercial sex partners during peacetime and deployment (Brodine et al, 2003;Larsen et al, 2004;Ryan et al, 1998). In addition to health-related behavior, environmental circumstances (such as the location of military bases, sex workers, and the nature of deployment/service) may influence sexual risk taking, and STI and HIV infection in military personnel.…”
mentioning
confidence: 99%